giải phương trình: [(3x -2) phần 6] -5 = [3-2(x+7) phần 4]

giải phương trình:
[(3x -2) phần 6] -5 = [3-2(x+7) phần 4]

2 bình luận về “giải phương trình: [(3x -2) phần 6] -5 = [3-2(x+7) phần 4]”

  1. Giải đáp+Lời giải và giải thích chi tiết:
    {3x-2}/{6}-5={3-2(x+7)}/{4}
    <=>{2.(3x-2)}/{12}-{12.5}/{12}={3.[3-2(x+7)]}/{12}
    <=>2.(3x-2)-12.5=3.[3-2(x+7)]
    <=>6x-4-60=9-6(x+7)
    <=>6x-4-60=9-6x-42
    <=>6x+6x=4+60+9-42
    <=>12x=31
    <=>x=31/12 
    Vậy S={31/12}

    Trả lời
  2. (3x-2)/6-5=(3-2(x+7))/4
    <=>(4(3x-2))/(24)-(120)/(24)=(6(3-2x-14))/(24)
    <=>4(3x-2)-120=6(-2x-11)
    <=>12x-8-120=-12x-66
    <=>12x+12x=-66+120+8
    <=>24x=62
    <=>x=(31)/(12)
    Vậy S={(31)/(12)}
     

    Trả lời

Viết một bình luận

Câu hỏi mới